2004
DOI: 10.1111/j.1365-313x.2004.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins play opposite roles in lateral root formation, and nematode and Rhizobial symbioses

Abstract: SummaryWe used the cytokinin-responsive Arabidopsis response regulator (ARR)5 gene promoter fused to a b-glucuronidase (GUS) reporter gene, and cytokinin oxidase (CKX) genes from Arabidopsis thaliana (AtCKX3) and maize (ZmCKX1) to investigate the roles of cytokinins in lateral root formation and symbiosis in Lotus japonicus. ARR5 expression was undetectable in the dividing initial cells at early stages of lateral root formation, but later we observed high expression in the base of the lateral root primordium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
199
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(212 citation statements)
references
References 51 publications
12
199
1
Order By: Relevance
“…Gheysen and Fenoll (2002) provide a detailed review of the approximately 50 genes known to be up-regulated and a few that are repressed. One emerging picture is that GCs share many features with rhizobial nodules, including coexpression of specific transcription regulators , early nodulation genes (Bird, 1996;Koltai et al, 2001;Favery et al, 2002), and cytokinin-responsive genes (Lohar et al, 2004); genetic data reinforce these similarities (Lohar and Bird, 2003;Bird, 2004;Weerasinghe et al, 2005). Numerous putative defense genes also are up-regulated during RKN infection, including peroxidases, chitinases, extensins, and proteinase inhibitors, perhaps as a global response to pathogen invasion.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Gheysen and Fenoll (2002) provide a detailed review of the approximately 50 genes known to be up-regulated and a few that are repressed. One emerging picture is that GCs share many features with rhizobial nodules, including coexpression of specific transcription regulators , early nodulation genes (Bird, 1996;Koltai et al, 2001;Favery et al, 2002), and cytokinin-responsive genes (Lohar et al, 2004); genetic data reinforce these similarities (Lohar and Bird, 2003;Bird, 2004;Weerasinghe et al, 2005). Numerous putative defense genes also are up-regulated during RKN infection, including peroxidases, chitinases, extensins, and proteinase inhibitors, perhaps as a global response to pathogen invasion.…”
mentioning
confidence: 84%
“…Various lines of evidence also have implicated auxin and cytokinin flux in the RKN-host interaction (Mathesius et al, 1998;Hutangura et al, 1999;Karczmarek et al, 2004;Lohar et al, 2004) as part of the regulation of root architecture. Thus, rather than focus on gene expression in GCs per se, we designed experiments to interrogate genes representative of the broader tomato root transcriptome during compatible and incompatible interactions with RKN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokinin is primarily synthesized in the root cap [69] and has a largely antagonistic effect to auxin in terms of root architecture: cytokinin has an inhibitory effect on lateral root branching, with mutants for cytokinin biosynthesis and sensitivity demonstrating increased numbers of lateral roots [70][71][72][73]. Auxin is synthesized primarily in young aerial tissues and undergoes polar transport towards the root tissues [74].…”
Section: Control Of Root Branching In Arabidopsis (A) Hormonesmentioning
confidence: 99%
“…Both kinases seem to become activated in early stages of nodules such as 2-day-old nodules in which nodule organogenesis including cortical cell division occurs (Oldroyd et al, 2011). The effects of phytohormones, especially auxin and cytokinin, have been reported to affect nodule organogenesis (Lohar et al, 2004;Oldroyd et al, 2011), and the activity of plant S6K1 was also found to be positively regulated by these hormones (Turck et al, 2004). Therefore, it seems probable that control of nodulation by these phytohormones is mediated through the activation of TOR signaling components.…”
Section: Resultsmentioning
confidence: 99%